Invasively measured and estimated central blood pressure using the oscillometric algorithm Antares in patients with and without obesity. - Alexander Stäuber; Marcus Dörr; Cornelia Piper; Marco Köster; Harald Lapp; Stefan Richter; Marc-Alexander Ohlow; Siegfried Eckert; Matthias Wilhelm Hoppe; Michael Thomas Coll Barroso; Johannes Baulmann (PLoS ONE, 2023)
Background Obesity is a global health concern and risk factor for cardiovascular disease. The assessment of central blood pressure (cBP) has been shown to improve prediction of cardiovascular events. However, few studies have investigated the impact of obesity on cBP in adults, and invasive data on this issue are lacking. This study aimed to evaluate cBP differences between patients with and without obesity, identify cBP determinants, and evaluate the accuracy of the algorithm Antares for non-invasive cBP estimation. Methods A total of 190 patients (25% female; 39% with BMI ≥30kg/m2; age: 67±12 years) undergoing elective cardiac catheterization were included. cBP was measured invasively and simultaneously estimated non-invasively using the custo screen 400 device with integrated Antares algorithm. Results No significant cBP differences were found between obese and non-obese patients. However, females, especially those with obesity, had higher systolic cBP compared to males (P<0.05). Multiple regression analysis showed that brachial mean arterial pressure, pulse pressure, BMI, and heart rate predicted cBP significantly (adjusted R2 = 0.82, P<0.001). Estimated cBP correlated strongly with invasive cBP for systolic, mean arterial, and diastolic cBP (r = 0.74-0.93, P<0.001) and demonstrated excellent accuracy (mean difference <5 and SD <8 mmHg). Conclusions This study discovered no significant difference in cBP between obese and non-obese patients. However, it revealed higher cBP values in women, especially those with obesity, which requires further investigation. Additionally, the study highlights Antares' effectiveness in non-invasively determining cBP in obese individuals. This could improve the diagnosis and treatment of hypertension in this special patient population.